2016
DOI: 10.1016/j.socscimed.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Social networks, social participation, and health among youth living in extreme poverty in rural Malawi

Abstract: Extensive research documents that social network characteristics affect health, but knowledge of peer networks of youth in Malawi and sub-Saharan Africa is limited. We examine the networks and social participation of youth living in extreme poverty in rural Malawi, using in-depth interviews with 32 youth and caregivers. We describe youth’s peer networks and assess how gender and the context of extreme poverty influence their networks and participation, and how their networks influence health. In-school youth h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
1
23
0
3
Order By: Relevance
“…Implications AGYW who are out of school experience relatively more psychological distress compared to their schoolattending peers [44]. As stated earlier, most mental health disorders are undiagnosed until adulthood [9][10][11].…”
Section: Strengths and Weaknessesmentioning
confidence: 90%
“…Implications AGYW who are out of school experience relatively more psychological distress compared to their schoolattending peers [44]. As stated earlier, most mental health disorders are undiagnosed until adulthood [9][10][11].…”
Section: Strengths and Weaknessesmentioning
confidence: 90%
“…Mental health disorders, particularly among adolescent girls and young women (AGYW), are generally under-researched in sub-Saharan Africa. Although there is limited literature on the topic, one study in Malawi suggested that AGYW who are out-of-school are at a higher risk of mental health disorders compared to their school-attending peers [18]. In Malawi, the risk factors for mental health disorders among AGYW who are out of school were poverty, daily hassles and limited social capital [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of constraints on time and funding, we did not implement the Photovoice components of collaboratively assigning topics with participants, involving participants in the analysis and/or write-up of the results, nor did we facilitate an action component like some (Carter-Edwards et al, 2015) in which study participants work to address jointly identified issues. Instead, based on previous experiences using in-depth interviews with adolescents in Malawi (Rock et al, 2016), we chose a photo-elicitation approach to involve adolescents in this context in a more engaging way as we describe below.…”
Section: Introductionmentioning
confidence: 99%